Keuntungan Maksimum Dan Skala Usaha Sub Sektor Kehutanan: Suatu Upaya Peningkatan Produktivitas Usaha Persuteraan Alam Dalam Perspektif Pembangunan Ekonomi - Nurdiana, Nurdiana; Hasan, Muhammad; Nuraisyiah, Nuraisyiah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
This study aims to assess the economic feasibility of natural business enterprises in Enrekang Regency in terms of income or business profits. This research is quantitative research. The results of this study indicate that the business scale of natural business enterprises in Enrekang Regency is not in constant returns to scale conditions, so that means that the utilization of resources or factors of production in natural business enterprises in Enrekang Regency can still be improved or developed